Adolescent pregnant women's health practices and their impact on maternal, fetal and neonatal outcomes: a mixed method study protocol - Tahere Hadian; Sanaz Mousavi; Shahla Meedya; Sakineh Mohammad-Al; Eesa Mohammadi; Mojgan Mirghafourvand (BMC, 2019)
Abstract Background Considering that individuals' health practices can affect the health of both mothers and babies, this study is designed to: (a) assess adolescent pregnant women's health practices and their relationship with maternal, fetal, and neonatal outcomes; (b) explore the perception of adolescent pregnant women about their own health practices; and (c) recommend some strategies to improve adolescent pregnant women's health practices during pregnancy. Methods/design This mixed-method study with the sequential explanatory design has two phases. The first phase (quantitative phase) is a prospective study to assess the adolescent pregnant women's health practices and its relationship with maternal, fetal, and neonatal outcomes who live in Tehran, the capital city of Iran. A cluster sampling method will be used to select 316 adolescent pregnant women who visit health centers in Tehran. The second phase is a qualitative study designed to explore the adolescent pregnant women's perception of important aspects and factors of health practices that can affect their health outcomes. In this phase, purposive sampling and in-depth individual interviews will be conducted for data collection. The conventional content analysis approach will be employed for data analysis. In addition to literature review and nominal group technique, the findings of the qualitative and quantitative phases, will be used to recommend some strategies to support adolescent pregnant women to improve their health practices during pregnancy. Discussion This is the first study looking into health practices in adolescent pregnant women which will be performed via a mixed-method approach, aiming to develop health practices improvement strategies. It is worth noting that there is no strategic guideline in Iran's health system for improvement of health practices of adolescents. Therefore, it is hoped that the strategy proposed in the current study can enhance health practices of adolescents during pregnancy and ultimately improve their pregnancy and childbirth outcomes. Ethical code IR.TBZMED.REC.1397.670.